Design of Management Architecture for Satellite-Terrestrial Integrated Networks - Xiang HAN; Tao DONG; Jie YIN; Zhihui LIU (天地一体化信息网络)
The management of the satellite-terrestrial integrated network targeting giant constellations and large-scale networks, requires the comprehensive management of heterogeneous infrastructure, layered stereoscopic network, cross domain multi-dimensional resources, customized business services, the collaboration and efficiency of management directly affect the service capability of the network.Based on the concept of network as its essence and collaboration between satellites and networks, this paper explored the collaborative manage mechanism of constellation, network, and business, proposed the overall architecture of satellite-terrestrial integrated network management, designed the manage center function in detail, planed typical operational management processes, and analyzed its applicability in the management of giant constellations in orbit and large-scale cross domain network management.This paper provided technical support for the construction and operation management of the satellite-terrestrial integrated network.